TATA KELOLA PUBLIK DAN SEKTOR KETIGA: TATA KELOLA, MANAJEMEN KONTRAK, DAN MANAJEMEN PUBLIK: Public Governance and the Third Sector: Governance, Contract Management, and Public Management - Candra, Edi; Nurdin , Nurliah (Universitas Serang Raya, 2024)
Problem: This study examines public governance and the role of the third sector in improving contract management effectiveness and the quality of public services. In the context of modern governance, the third sector (non-profit organizations, NGOs, and community-based institutions) increasingly plays a vital role as a government partner in providing public services, particularly in social sectors such as health, education, and social welfare. Purpose: This study aims to analyze the relationship between governance, contract management, and public management in the public sector, with a focus on effectiveness and efficiency in contract management within government institutions. Methodolgy: Using a qualitative descriptive approach, this research explores various factors influencing the success of contract management in the public sector, including challenges encountered and the steps required to enhance sound governance. Primary data were collected through in-depth interviews with government officials, project managers, and third-party providers partnering with the government, while secondary data were gathered from official documents, annual reports, public policies, and relevant literature. Analysis was conducted using a thematic approach to identify patterns or main themes related to governance practices and contract management. Results/Findings: The findings indicate that role clarity, transparency, and effective communication are key factors influencing the success of partnerships between the government and the third sector. Additionally, challenges such as organizational culture differences, resource limitations, and contract management ambiguities impact public service quality and public trust. Addressing these challenges requires improved governance through structured performance measurement, leadership support, and strong coordination between the government and third parties. This study provides practical recommendations to strengthen accountability and efficiency in public sector contract management, aiming to enhance the quality of public services and public trust in the government.